Case report: Transcatheter valve repair with Cardioband: a new treatment option for secondary tricuspid regurgitation in cardiac transplant patients. Issue 6 (13th December 2020) - Wösten, Monique; Baldus, Stephan; Pfister, Roman
Abstract: Background: Tricuspid regurgitation (TR) is the most frequent valvular complication after cardiac transplantation. As in native hearts, the role of surgical therapy particularly in secondary TR is unclear due to high procedural risk and unsatisfying results. Currently, percutaneous techniques are under development for TR repair with less procedural risk and promising preliminary results. Case summary: We present a 67-year-old man who underwent heart transplantation (biatrial anastomosis) because of ischaemic heart disease 15 years ago and aortic valve replacement in 2010. Because of progressive severe dyspnoea (New York Heart Association Class III) in 2018 and signs of right heart failure with ascites he underwent transthoracic echocardiography which showed normal graft function, but massive TR of functional aetiology. The heart team decision was an interventional approach using the Cardioband System (Edwards Lifesciences) to treat TR based on the high risk associated with a third cardiac surgery and impaired right ventricular function. The procedure was performed in general anaesthesia with transoesophageal echocardiography and fluoroscopic guidance. Tricuspid regurgitation improved from massive to mild with a mean pressure gradient of 2.9 mmHg. Discussion: This is the first case report of Cardioband implantation in tricuspid position in a heart transplant patient with the good technical and clinical result, suggesting that this technique might offer a treatment option to highly selected post-transplant patients with secondary severe TR and high surgical risk.